Outsourcing Strategies of Mining Industries: An Empirical Evidence from a Developing Nation - John Mensah; Frank Obeng; Stephen Kwasi Anim (International Journal of Supply Chain Management, 2015)
The future of gold mining depends on continually searching for cheaper and more efficient ways of mining. Businesses, both the private and the public sectors alike are now into outsourcing practices. It is a phenomenon that has seemingly come to stay with the legitimate recognition as a business practices. The main objective of the study is to explore the factors responsible for efficient outsourcing decision in the mining industry in the Sub Saharan Africa. The study is an exploratory case study of Goldfields Ghana Limited-Tarkwa. Out of seventy-three respondents contacted, a total of 55 questionnaires were distributed, and there were 33 usable questionnaires returned. Both descriptive and inferential statistical techniques were employed in analysing data using the SPSS 20. In relation to the Critical Factors for a Successful Outsourcing, the study revealed that a strong agreement was among respondents in favour of benchmarking vendors capabilities and technical excellence as the most important factor to consider prior to any outsourcing decision. Again, it was realized that, the factors that align with meeting the strategic fit of the outsourcer as a critical for outsourcing was predominantly ranked next to the most successful factor. It therefore recommended that, for a successful outsourcing operation, it is important to form contracts so that the supplier acts with the outsourcers best interest in mind. Different contract terms influence the vendors actions, such as their capacity decisions.